STRATEGI DHAMMADUTA DALAM MENINGKATKAN KEYAKINAN UMAT BUDDHA DI KABUPATEN BLITAR - Ananda Giri, I Made Dwi; Sentot, Santacitto; Budiyanto, Khemadharo Sigit (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2021)
This study was conducted to determine the strategy of Dhammadūta in increasing the belief of Buddhists in the Blitar Regency. Due to the ineffectiveness of coaching activities in the Blitar Regency, the Dhammadūta activity was formed as an effort to deal with the problems of Buddhists in the area. Meanwhile, the Dhammadūta strategy is based on SWOT analysis (Strength, Weakness, Opportunity, and Threat). The design of this research is qualitative research using a qualitative descriptive study method. The instrument used is a list of interviews that were asked of two key informants and eight supporting informants and analyzed using the Huberman, Miles, & Saldaña model analysis through three stages, namely data condensation, data presentation, and conclusion/verification. The result of this study indicates that Dhammadūta in the Blitar district has a coaching strategy, that is, by strengthening the quality of Dhammadūta itself, As is the case with holding Buddhist education and training activities and public speakers. It is known that with the existence of Dhammadūta activities, Buddhists in the Blitar district are becoming more active in coming to the monastery to develop their spiritual qualities. Thanks to these activities, the faith of Buddhists in the Blitar district has increased. Thus, there has been harmony between the increasing quality of Dhammadūta and the increasing belief of Buddhists in the Blitar Regency.